Synthesis and characterisation of carbon nanotubes from hydrocarbon-rich flames - Tan, Win Hon, 1990- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Doktor Falsafah (Kejuruteraan Mekanikal))